Educating the strength and hope in school (Journal of Parents and Teachers, 2012)
In this article the school appears to be the perfect place to educate children and for them to learn positive values such as strength and hope, values that allow the healthy development of the person. The school can incorporate in his scholar curriculum this educational process by including methodologies and actions that boost the student’s vision and actions of resilience. These are the actions and methodologies chosen to include because they are the key capacities that a person uses to confront difficult situations successfully in life. In addition, positive psychology is a theoretical frame used to explain how it is possible to educate children in strength and hope in the school and in the family. nt--> ención hasta la década de los noventa. La tendencia era estudiar aquello que amenaza el bienestar del ser humano, llevando a centrar el interés en déficits y problemas. Las personas que desarrollan sus fortalezas y capacidades, mejoran su calidad de vida y previenen la aparición de trastornos. Además, la percepción de eficacia y bienestar, aumentan al mismo tiempo que la motivación. Es por eso que nos parecen relevantes y porque aumentan la sensación de alegría. Los padres y maestros tenemos una gran responsabilidad de enfocarnos  más hacia las capacidades de nuestros hijos y alumnos, que hacía los déficits y limitaciones. Es un estilo que se aprende, y así ellos también ellos serán más hábiles en reconocer, utilizar y desarrollar sus fortalezas en el presente y también en el futuro.
Keywords: Methodology; Cooperation; Participation; Afection.; values ​​education